A novel approach for efficient resource allocation in 6G V2V networks using neighbor-aware greedy algorithm and sweep line model - Spandana Mande; Nandhakumar Ramachandran (Egyptian Informatics Journal)
Advances in vehicular networks are attracting the attention of academic institutions and corporate groups who see them as a means of facilitating smart cities, autonomous driving, and the Intelligent Transportation System (ITS). This system can display highly dynamic features because of its portability and speed. The growing number of applications is placing pressure on 6G vehicle networks’ Quality of Service (QoS). A new era of customized user experiences, significantly increased road safety, and vehicle-to-vehicle (V2V) communication is quickly approaching with the introduction of connected autonomous vehicles. To achieve this ambitious goal, a greatly improved vehicle-to-everything (V2X) communication network is required, one that can facilitate massive data interchange rapidly, extremely reliably, and with low latency between vehicles and Road Side Units (RSUs). V2X is vulnerable to resource depletion because of its low processing capacity, which can result in harmful delays in communication between V2V, V2V and RSU, and RSU and ITS. This work analyses a sweep line algorithm that utilizes the concept of a sweep area to address issues in Euclidean space for enhanced V2V communication. In our research, we present an Enhanced Neighbor Node Associated Greedy-based Resource Distributed V2V Model with Sweep Line Model (NNAGbRD-V2V-SLM) for secure resource handling and management in V2V and V2X communication. The resource distribution strategy for V2V users participating in the exchange of information is based on the greedy method. The recommended algorithm determines which resource is optimal for each V2V user by taking a multi-level approach. The proposed model shows better resource management efficiency when compared to the current approach.